EVALUACIÓN DE DESEMPEÑO DOCENTE Y SU INFLUENCIA EN LA MEJORA DE LA ENSEÑANZA - AVILES SANTOS, GELEN XIOMARA (2024)
The objective of this research was to analyze the evaluation of teaching performance and its impact on the improvement of teaching for 7th "A" grade students of the Abdón Calderon Muñoz Educational Unit. It addressed the issue of educational quality and the importance of continuous evaluation of teaching work in the improvement of teaching and learning processes. Mixed data collection techniques were used, including student surveys and teacher interviews. The results revealed that most students perceive the teacher's explanations as clear and understandable, and value the organization of the classes. However, they identified areas for improvement in the use of didactic material and the availability of the teacher to resolve doubts outside class hours. In addition, it was evidenced that the evaluations proposed by the teacher are perceived as adequate by most of the students, although there are some discrepancies in this aspect. The importance of strengthening teacher training and promoting support and feedback strategies to improve the quality of teaching is highlighted. It is suggested to implement professional development programs, foster collaboration between teachers and students, and integrate educational technologies in the classroom. These actions can contribute significantly to the continuous improvement of educational processes and the achievement of better academic results.